HUBUNGAN STATUS GIZI DENGAN PENINGKATAN KEJADIAN PREMENSTRUAL SYNDROME (PMS) PADA MAHASISWI JURUSAN KEBIDANAN POLTEKKES KEMENKES BANJARMASIN - Nur Rohmah Prihatanti (Sekolah Tinggi Ilmu Kesehatan Mitra Husada Karanganyar, 2022)
ABSTRACT Premenstrual Syndrome (PMS) is a collection of affective and physical symptoms that develop during the luteal phase of the menstrual cycle and disappear within a few days of menstruation. Complaints of Premenstrual Syndrome (PMS) can be in the form of headaches, abdominal pain, breast pain, anxiety, fatigue, loss of energy, difficulty sleeping, and difficulty concentrating. The prevalence of Premenstrual Syndrome (PMS) reaches 90% of the entire population of women of childbearing age in the world and in Indonesia it reaches 85%. The incidence of Premenstrual Syndrome (PMS) can increase because it is influenced by several risk factors, one of which is nutritional status. The study was conducted using a cross sectional approach with an analytical observational design. The research was conducted at the Midwifery Department of the Health Poltekkes of the Ministry of Health Banjarmasin in August-December 2021 with a population of all third semester students of the three diploma study program majoring in midwifery Poltekkes Ministry of Health Banjarmasin in the 2021/2022 academic year, which is as many as 40 people. The sample selection used a simple random sampling method where the sample was taken randomly from the population with the requirement that they had experienced menstruation. The sample was calculated using the Slovin formula and the number of samples was 35 people. The independent variable is nutritional status with the research instrument in the form of Body Mass Index (BMI) and the dependent variable is Premenstrual Syndrome (PMS) with the research instrument in the form of The Shortened Premenstrual Assessment Form (SPAF) questionnaire. From the results of a chi-square pearson test, the results of the calculation of p-value = 0,000 or the value of Sig.=0,000 ≤ α=0,05, which means that there is a correlation between nutritional status and an increase in the incidence of Premenstrual Syndrome (PMS) in Midwifery Department students, Poltekkes, Ministry of Health, Banjarmasin. Keywords: Student, Premenstrual Syndrome (PMS), Nutritional Status ABSTRAKPremenstrual Syndrome (PMS) merupakan kumpulan gejala afektif dan fisik yang berkembang selama siklus menstruasi fase luteal dan menghilang dalam beberapa hari selama menstruasi. Keluhan Premenstrual Syndrome (PMS) dapat berupa nyeri kepala, nyeri perut, nyeri payudara, cemas, lelah, hilang energi, susah tidur, dan sulit berkonsentrasi. Prevalensi Premenstrual Syndrome (PMS) mencapai 90% dari seluruh populasi wanita usia subur di dunia dan di Indonesia mencapai 85%. Kejadian Premenstrual Syndrome (PMS) dapat meningkat karena dipengaruhi oleh beberapa faktor risiko salah satunya yaitu status gizi. Penelitian dilakukan menggunakan pendekatan cross sectional dengan desain observasional analitik. Penelitian dilakukan di Jurusan Kebidanan Poltekkes Kemenkes Banjarmasin pada bulan Agustus-Desember 2021 dengan populasi seluruh mahasiswi semester tiga program studi diploma tiga jurusan kebidanan Poltekkes Kemenkes Banjarmasin tahun ajaran 2021/2022 yaitu sebanyak 40 orang. Pemilihan sampel menggunakan metode simple random sampling dimana sampel diambil secara acak dari populasi dengan persyaratan sudah mengalami menstruasi. Sampel dihitung menggunakan rumus Slovin dan didapatkan jumlah sampel sebanyak 35 orang. Variabel independen adalah status gizi dengan instrumen penelitian berupa Indeks Massa Tubuh (IMT) dan variabel dependen adalah Premenstrual Syndrome (PMS) dengan instrumen penelitian berupa kuesioner The Shortened Premenstrual Assesment Form (SPAF). Dari hasil uji pearson chi-square, diperoleh hasil perhitungan p-value = 0,000 atau nilai Sig.=0,000 ≤ α=0,05 yang artinya terdapat hubungan antara status gizi dengan peningkatan kejadian Premenstrual Syndrome (PMS) pada mahasiswi jurusan kebidanan Poltekkes Kemenkes Banjarmasin. Kata Kunci: Mahasiswi, Premenstrual Syndrome (PMS), Status Gizi